The Effects of Compensation and Benefit Satisfaction on Turnover Intention - Mustika, Mawar; Prihanto, Y. Johny Natu; Winarno, P.M. (Conference Series, 2021)
Most organizations now operate in a VUCA world. Companies must deal with challenges to find out how to effectively manage the talent. Many companies have difficulty reducing the turnover rate of employees. Some companies believe in minimizing employee turnover intention by providing attractive compensation and benefits. This study aims to see how compensation and benefits can reduce turnover intention through perceived organization support and affective organization commitment. This study adopted quantitative research methods; with 357 total samples, data were collected using the snowball sampling technique. Smart Pls SEM was used to analyze the data. The results showed, there was indeed a negative correlation between satisfaction with compensation and benefits on turnover intention through perceived organization support and affective organization commitment. As a practical implication, the company can see compensation and benefits factors the most influence reducing turnover intention, the originality of this study for adopted a second-order approach analysis.